The Impact of University Students’ Personal Values and Moral Cognition on Their Perception of Social Responsibility - Hao Sun; Krittavit Bhumithavara (Al-Qalam Institute, 2025)
In the context of growing global attention to social responsibility, understanding the factors that shape university students’ sense of social responsibility has become increasingly important. This study aims to examine the influence of personal values and moral cognition on students’ perceptions of social responsibility and to explore the mediating role of ethical orientation. Using a quantitative approach supported by qualitative insights, data were collected from full-time university students through structured questionnaires and in-depth interviews, and analyzed using statistical techniques. The findings reveal that multiple dimensions of personal values significantly influence idealism and are strongly correlated with relativism. Furthermore, idealism, relativism, and ethical orientation significantly affect social responsibility cognition, with ethical orientation strengthening the influence of moral cognition on perceptions of social responsibility. This study contributes a comprehensive analytical framework linking personal values, moral cognition, and social responsibility, offering empirical evidence that enriches moral psychology and educational research. The results suggest that universities should integrate value education and ethical reasoning into curricula to foster socially responsible attitudes and support the development of morally grounded future professionals.